1
$\begingroup$

I am given the PDE:

$$u_x+u_y+u=e^{x+2y} \quad u(x,0)=0$$

I tried to do this using the method of the characteristics in the following way.

First I find the particular solution of this inhomogenous equation by substituting $u_p = Ae^{x+2y}$ giving me $A=\frac{1}{4}$ hence $$u_p=\frac{1}{4}e^{x+2y}$$

Now I try the homogenous equation

$$u_x+u_y+u=0$$

If I parameterize $x,y$ with $t$ and have now $u(x(t),y(t))$ I can write

$$\frac{du}{dt} = \frac{dx}{dt}\frac{\partial u}{\partial x} + \frac{dy}{dt}\frac{\partial u}{\partial y} $$

So equating like terms I have

$$\frac{dx}{dt}=1 \quad \frac{dy}{dt}= 1 \quad \frac{du}{dt}=-u$$

My initial conditions are $x(t=0)= x_0, y(t=0)=0$ and $u(t=0)=u(x(0),y(0))=u(x_0,0)=0$

So then I can solve these equations to get

$$x = t + x_0 \Rightarrow x_0=x-t \quad y = t \quad u = Ce^{-t}$$

Now I'm not 100% sure what $C$ should be but I assume it some function of the initial condition, i.e

$$u=F(x_0)e^{-t} \Rightarrow u=F(x-t)e^{-t} \Rightarrow u_0 = F(x_0)=0 ?$$

But the initial condition is $u_0 = 0$ so $u$ is $0$ at all $x$??

I'm getting stuck here but I followed similar method on other examples given and it works fine. Why is this initial condition $0$ giving me $u=0$, what am I missing?

$\endgroup$
  • $\begingroup$ Note that you modified $u$ to the homogeneous part by subtracting a particular solution. You need to remove the particular solution also from the initial condition to get the IC for the homogeneous part. $\endgroup$ – LutzL May 25 at 18:00
  • $\begingroup$ @LutzL Why is that? I dont see that in my notes. I tried now with that and it works, do you have some reference or website i can see why this theory works? I mean by subtracting particular solution from IC? And I subtracted $e^{x+2y}$ which is not the particular solution, it is $4 \times \frac{1}{4}e^{x+2y}$, so a constant times the particular solution. So do I subtract $e^{x+2y}$ from the IC or $\frac{1}{4}e^{x+2y}$ $\endgroup$ – hh4346 May 25 at 18:40
2
$\begingroup$

You decompose your solution as $u=u_h+u_p$ where you determined $u_p$ per undetermined coefficients as $u_p(x,y)=\frac14e^{x+2y}$. Then indeed as constructed $$ (u_h)_x+(u_h)_y+u_h=0. $$ However, also in the initial condition you must reflect this decomposition to get $$ 0=u(x,0)=u_h(x,0)+u_p(x,0)\implies u_h(x,0)=-\frac14e^x. $$


Now as you found $u_h(x,y)=F(x-y)e^{-x}$, this leads in the initial conditions to $F(x)=-\frac14e^{2x}$ and thus $$ u(x,y)=-\frac14e^{2(x-y)}e^{-x}+\frac14e^{x+2y}=\frac12e^x\sinh(2y). $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.